Pengaruh Pemberian Ankle Strategy Exercise Terhadap Keseimbangan Dinamis Pada Lansia Di Kelurahan Persiakan Kecamatan Padang Hulu Tebing Tinggi - Dinda Hanifah; Dewi Agustina; Sulaiman Sulaiman (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Decreased muscle strength is estimated at 1%-3% per year. Changes in the nervous and sensory systems also affect the balance of the elderly. Objective: To determine the effect of giving ankle strategy exercise on dynamic balance in the elderly in the village of Persiakan, District of Padang Hulu Tebing Tinggi. Methods: This research is pre-experimental with one group pretest-posttest design. Determination of the sample using purposive sampling technique with a total of 30 people aged 60-74 years. Dynamic balance is measured by the Timed Up and Go Test. The ankle strategy exercise was carried out 12 times (3 times a week) for 1 month. Results: Before giving the ankle strategy exercise, it was found that the elderly had a